mHealth App for Cannabis Users: Satisfaction and Perceived Usefulness - Monney, Grégoire; Penzenstadler, Louise; Dupraz, Olivia; Etter, Jean-François; Khazaal, Yasser (Frontiers in Psychiatry, 2015)
Objective: The aim of this study was to describe the characteristics of cannabis users and their levels of satisfaction with Stop-cannabis, an app intended for cannabis users who want to stop or reduce their cannabis use or prevent relapse. Methods: A cross-sectional online survey was administered to users of Stop-cannabis, a French-language app for iOS and Android devices. All app users were invited to participate in the survey via a message sent to the app. Results: For hundred and eighty-two users answered the survey. The app was used daily by 348 of the participants (around 70%). More than 80% of participants (397) considered the app to have helped them “a little” or “a lot” to stop or reduce cannabis consumption. Most of the users’ suggestions were related to the number or the quality of the messages sent by, or displayed in, the app. Conclusion: This pilot study supports the feasibility of such an app and its perceived usefulness. A self-selection bias however limits the conclusions of the study. The efficacy of the app should be evaluated in a randomized controlled trial.